Menguji Keberpihakan Al-MishbâH̲ Pada Syî’ah: (Studi Kritis Atas Penilaian Afrizal Nur Pada TafsîR Al-Mishbâh̲ Karya M. Quraish Shihab) - Mustakim Mustakim; Nur Rofiah; Kerwanto Kerwanto (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to examine in depth the views of Afrizal Nur in his book Tafsir Al-Mishbâh̲ in Sorotan which assesses that M. Quraish Shihab has a strong affiliation with the Shia school. The author uses the theory of hermeneutics of objectivity, where the interpretation of the text is understood based on the author's intent, not the subjective conclusions of the interpreter. The findings of this study indicate that although M. Quraish Shihab cites Shia sources of interpretation, he remains objective in processing the references. The analysis proves that some of M. Quraish Shihab's views in Tafsir Al-Mishbâh̲ often contradict Shia figures, such as Thabathaba'i in Tafsir al-Mîzân. This study also discusses the main issues highlighted by Afrizal Nur, including the glorification of Fatimah R.A., the successor of the Prophet Muhammad SAW, to the concepts of Ahl al-Bait, ismah, and taqiyyah. With the maudhû’i interpretation model and qualitative approach, this study successfully explains that Afrizal Nur’s view is not entirely objective in assessing the Tafsir Al-Mishbâh̲. Through concrete examples of verses and themes of interpretation, this study strengthens the argument that M. Quraish Shihab maintains the scientificity of his interpretation without supporting certain sectarian views